2021
DOI: 10.1111/cobi.13758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experience with access regimes on stewardship behaviors of small‐scale fishers

Abstract: Article impact statement: Experimental evidence supports the role of collective, exclusive access regimes in determining natural resource users' stewardship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…Generalization across cultures presents a higher hurdle for the external validity of games, suggesting studies should be carried in the field, taking into account context and culture. We do not test the external validity of our results explicitly, but our results are consistent with previous research using common-pool resource games, and encompassing some of the same fishing communities, that showed pro-social behavior was linked with well-functioning fishing association 18,30 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Generalization across cultures presents a higher hurdle for the external validity of games, suggesting studies should be carried in the field, taking into account context and culture. We do not test the external validity of our results explicitly, but our results are consistent with previous research using common-pool resource games, and encompassing some of the same fishing communities, that showed pro-social behavior was linked with well-functioning fishing association 18,30 .…”
Section: Discussionsupporting
confidence: 84%
“…These studies likely misrepresented the behavior of people who are not formally educated, affluent students. While the trend has changed in the last decade, with several studies carried out in the field and in developing countries, studies in fishing communities are rare and often have been limited to public goods 12,13,18,19 ; very few studies have examined trust and reciprocity games or bargaining games 20 . As such, further work in communities that rely on and are involved in managing common-pool resources is necessary.…”
mentioning
confidence: 99%
“…For example, in each round, participants decide how much of a shared resource they would like to harvest and the availability of the resource depends on how much was harvested in the previous round (Schill et al, 2015). Such dynamic experimental designs allow for the capture of social–ecological interactions over time (Cardenas et al, 2013; Lindahl et al, 2021; Rivera‐Hechem et al, 2021).…”
Section: Methods For Analysing Interactions and Outcomesmentioning
confidence: 99%
“…To tackle these biases, we implemented a game-theory-based experiment in which all the students of a given class play a dyadic social dilemma with each classmate. Social dilemmas have been studied from a theoretical ( Boyd et al., 2003 ; Nowak, 2006 ; Guzmán et al., 2007 ; Delton et al., 2011 ; Santos et al., 2012 ; Capraro and Perc, 2021 ; Perc, 2016 ) and an experimental point of view ( Rivera-Hechem et al., 2021 ; Fehr and Gächter, 2000 ; Fehr and Leibbrandt, 2011 ), which have contributed enormously to the understanding of the dynamics of human cooperation. A new body of literature has shown that cooperative social norms that are prevalent in the real world can penetrate laboratory behavior ( Camerer, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who are more cooperative in the real world also behave more cooperatively in the lab ( Carpenter and Seki, 2011 ; Algan et al., 2013 ); and groups who achieve higher levels of cooperation in the real world also achieve higher levels of aggregate cooperation when playing a social dilemma in the lab ( Fehr and Leibbrandt, 2011 ; Gelcich et al., 2013 ; Hopfensitz and Miquel-Florensa, 2017 ). The social domain of all of these experimental studies ranges from the fishers of Toyama Bay ( Fehr and Leibbrandt, 2011 ) through the exploitation of benthic resources on the Chilean coast ( Rivera-Hechem et al., 2021 ) to the Wikipedians ( Algan et al., 2013 ). While all the above-referenced studies involved anonymous interactions, recent studies have shown that non-anonymous interaction increases cooperation in contrast with anonymous interaction, suggesting that pre-existing social connections affect laboratory behavior ( Wang et al., 2017 ; Conte, 2022 ).…”
Section: Introductionmentioning
confidence: 99%